Strategies Applied By The Lecturer To Cope With The Problems Faced By The Students In Learning Speaking At Muhammadiyah University Of Surakarta - ERDINA, PUTRI, Drs. Djoko Srijono, M.Hum, Aryati Prasetyarini, S.Pd, M.Pd (2015)
This research aims at describing the strategies applied by the lecture, identifying the problems faced by the students in learning speaking, and problems faced by the lecturer in Speaking 2 at Muhammadiyah University of Surakarta in 2014/2015 academic year. The object of this study is the strategies used by the lecturer of the Speaking 2 of Muhammadiyah University of Surakarta. The subject of this study is the lecturer and the students in Speaking 2 D of Muhammadiyah University of Surakarta. In analysing data the writer applied descriptive reserach consisting of reducing the data, displaying the data, and drawing conclusion. The result of the research shows that: 1) the problems faced by the lecturer in teaching speaking are students motivation, the use of mother tongue in English class, student's problem in preparing the material, and low participation. 2) the problems faced by the students in learning speaking are limitednumber of vocabulary and pronunciation, limited preparation, and forming a group. The strategies applied by the lecturer cope were problems are a) giving feedback, evaluation, rewards, and motivation, b) keeps students speaking the target language and evaluationc) giving flexible theme ang short time to drama perform, d) giving some instructions or training in discussion skill, e) the lecturer gives consult, motivation, feedback, evaluation, rewards, make a different topic, based on the activity on easy language, and keep the students speaking the target language, f) the lecturer encourages for each group, g) the lecturer gives advice to switch their member.